Levels of lysine and methionine+cystine for growing New Zealand White rabbits - Monteiro-Motta,Ana Carolina (2013)
Two experiments were carried out to evaluate, respectively, nitrogen balance (NB) and the productive performance of 31-to-50-day-old rabbits subjected to different levels of lysine and methionine+cystine (met+cys). Seventy-five animals were randomly distributed in 5 × 3 blocks (five levels of lysine: 5.5, 6.5, 7.5, 8.5 and 9.5 g/kg combined with three levels of met+cys: 5.0, 6.0 and 7.0 g/kg), with 15 treatments and five replications for the NB assay. The assay lasted 14 days: 10 days for acclimatization and four days for feces and urine collection. Increasing met+cys levels had a quadratic effect on the nitrogen excreted in urine (NU): the lowest excretion was found at the dietary level of 5.9 g/kg met+cys. Increasing lysine levels also affected NU and nitrogen retained daily (NR): the lowest NU was obtained at the dietary level of 7.28 g/kg lysine, and maximum NR was found at 7.24 g/kg lysine. Increases in met+cys levels in the diets affected neither performance nor carcass characteristics of rabbits up to 50 days of age. On the other hand, body weight at 50 days, daily weight gain and feed conversion of rabbits slaughtered at 50 days had a quadratic effect as the lysine levels increased. The best results were found at 7.5, 7.38 and 7.36 g/kg lysine. Lysine and met+cys levels of 7.4 and 5.0 g/kg in the diet are recommended for 31-to-50-day-old rabbits.